Ship aerosol emissions and marine fuel regulations: Impacts on physicochemical properties, cloud activity and emission factors - Escusa Dos Santos, Luis Filipe; Thomson, Erik S. (University of Gothenburg, 2024)
This data set includes measurement data from laboratory engine experiments where different fuel types and exhaust wets scrubbing was investigated for their impact on engine exhaust particle formation. Data includes information on particle number size distributions, effective densities, chemical characterization, hygroscopicity and ice nucleation activity of exhaust particles.

Detta dataset innehåller mätdata från motorexperiment i laboratorium. För mer detaljerad beskrivning se engelsk text.
Ship aerosol emissions and marine fuel regulations: Impacts on physicochemical properties, cloud activity and emission factors
Keywords: AEROSOLS; fuel; bränsle; aerosol chemistry; exhaust emission; hygroscopicity; nucleation; particle size distribution; ships; Environmental Sciences; Miljövetenskap